Decision-making in sports: the role of attention, anticipation and memory - José Afonso; Júlio Garganta; Isabel Mesquita (Universidade Federal de Santa Catarina, 2012)
Expertise is a core goal for the achievement of elite-level performances. In sport, expertise is deeply related to the ability of making accurate decisions. In this context, decision-making becomes highly complex, due to a large number of relevant cues and interactions, as well as to multiple non-linear cause-and-effect relationships and severe time pressure. In this paper, three core components underlying decision-making were analyzed: attention, anticipation, and memory. They were explored within high-complexity contexts. The goals of this review were to: (i) provide a sound knowledge and contextual framing for the concepts of attention, anticipation, and memory in the context of decision-making in sports; and (ii) analyze how their effects vary according to situational constraints. Analysis of the literature allowed highlighting that, in sports, attention should be mainly goal-driven, selective, with external broadband focus. Anticipation, a tenet for attaining elite-level performances, is justified when it doesn't increase the rate of errors and is sensitive to counter-communication strategies applied by the opponents; therefore, certain contexts invite the players to adopt waiting strategies, especially when the risk taken by anticipation leads to a reduction in effectiveness. Memory provides a solid basis for attention and anticipation, and also originates and supports intuitive and strategic thinking. The knowledge obtained potentiates a better-calibrated perception of relevant variables for decision-making, therefore enhancing the contribution of scientific research towards practice.